The life and adventures of Robinson Crusoe - Defoe, Daniel, 1661?-1731.; Rhead, Louis, 1857-1926; Rhead, F. A. (Frederick Alfred), 1855-- (Charlottesville, Va. : Core Knowledge Foundation, 1997)
During one of his several adventurous voyages in the 1600s, an Englishman becomes the sole survivor of a shipwreck and lives for nearly thirty years on a deserted island.
"Robinson Crusoe"--Cover.
"Daniel Defoe's classic abridged for young readers ; introduction by E.D. Hirsch, Jr."--Cover.
Keywords: Crusoe, Robinson (Fictitious character) -- Juvenile fiction; Shipwrecks -- Fiction; Survival -- Fiction; Adventure fiction